Private-public alliances for export development : the Korean case - Yoo Soo Hong (UN ECLAC SantiagoCL, 2010)
Presents the development path of Korea, from a country which started its development with a lack of natural resources, industrial facilities, sufficient foreign reserves and business experiences and with human resources as its only productive factor at its disposal; to its successful technological catch-up, export performance and economic development. Tries to find some helpful benchmarks for Latin American economies from a case study of Korea.